Arabidopsis dth9 Mutation Identifies a Gene Involved in Regulating Disease Susceptibility without Affecting Salicylic Acid–Dependent Responses - Mayda, Esther; Mauch-Mani, Brigitte; Vera, Pablo (My University, 2000)
To determine which components of the plant defense response make important contributions to limiting pathogen attack, an M2 mutagenized population of a transgenic Arabidopsis line was screened for mutants showing constitutive expression of ß-glucuronidase activity driven by the promoter region of the CEVI-1 gene. The CEVI-1 gene originally was isolated from tomato plants and has been shown to be induced in susceptible varieties of tomato plants by virus infection in a salicylic acid–independent manner. We report here the characterization of a recessive mutant, detachment9 (dth9). This mutant is more susceptible to both virulent and avirulent forms of the oomycete Peronospora and also exhibits increased susceptibility to the moderately virulent bacterial pathogen Pseudomonas syringae pv maculicola ES4326. However, this mutant is not affected in salicylic acid metabolism and shows normal expression of pathogenesis-related (PR) genes after pathogen attack. Furthermore, after inoculation with avirulent pathogens, the dth9 mutant shows a compromised systemic acquired resistance response that cannot be complemented by exogenous application of salicylic acid, although this molecule is able to promote normal activation of PR genes. Therefore, the dth9 mutation defines a regulator of disease susceptibility that operates upstream or independently of salicylic acid. Pleiotropy is also evident in the dth9 mutant in the sense that the shoots of dth9 plants are insensitive to the exogenously applied auxin analog 2,4-dichlorophenoxyacetic acid.